Personal history - Graham, Katharine, 1917- (New York : A.A. Knopf, 1997)
An extraordinarily frank, honest, and generous book by one of America's most famous and admired women - a book that is, as its title suggests, both personal and history. It is the story of Graham's parents: the multi-millionaire father who left private business and government service to buy and restore the down-and-out Washington Post; the aggressive, formidable, self-absorbed mother, known in her time for her political and welfare work, and her passionate friendships with men such as Thomas Mann and Adlai Stevenson. It is the story of how The Washington Post struggled to succeed - a fascinating and instructive business history told from the inside (the paper has been run by Graham herself, her father, her husband, and now her son). It is the story of Phil Graham - Kay's brilliant, charismatic husband (he clerked for two Supreme Court justices), whose plunge into manic-depression and eventual suicide are movingly and charitably recounted.
And, best of all, it is Kay Graham herself - brought up in great wealth, yet understanding nothing of money; half Jewish, yet - incredibly - unaware of it; naive, awkward, yet intelligent and energetic, and married to a man she adored. How he fascinated and educated her, and then in his illness turned from her and abused her, destroying her confidence and her happiness, is a drama in itself, followed by the rarer drama of her new life as the head of a great newspaper and a great company - a woman famous (and feared) in her own right. In other words, here is a life that came into its own with a vengeance - a success story on every level.
Includes index.
Keywords: Graham, Katharine, -- 1917-; Washington post (Washington, D.C. : 1974) -- History; Publishers and publishing -- United States -- Biography; Newspaper publishing -- Washington (D.C.) -- History -- 20th century